Sie sind auf Seite 1von 67

Introduction to Functions

Definition of Function: Domain, Co-domain and Range

Function can be easily defined with the help of the concept of mapping. Let X and Y
be any two non-empty sets. "A function from X to Y is a rule or correspondence that
assigns to each element of set X, one and only one element of set Y". Let the
correspondence be 'f' then mathematically we write f:X → Y

where

y = f(x), x ε X and y ε Y. We say that 'y' is the image of 'x' under 'f' (or x is the pre
image of y).

Two things should always be kept in mind:

(i) A mapping f: X → Y is said to be a function if each element in the set X has its
image in set Y. It is possible that a few elements in the set Y are present which are
not the images of any element in set X.

(ii) Every element in set X should have one and only one image. That means it is
impossible to have more than one image for a specific element in set X. Functions
can't be multi-valued (A mapping that is multi-valued is called a relation from X to Y)

• Set 'X' is called the domain of the function 'f'.


• Set 'Y' is called the co-domain of the function 'f'.
• Set of images of different elements of set X is called the range of the
function 'f'. It is obvious that range could be a subset of co-domain as we may have
few elements in co-domain which are not the images of any element of the set X (of
course these elements of co-domain will not be included in the range). Range is also
called domain of variation.

The set of values for which a function is defined is called the domain of the function.
The range of the function is the set of all images of domain of f. In above example,
the set A is the domain of the function f. B is not range but the co-domain of the
function. The range is the subset of the co-domain. The domain and the range of
a function may be an interval, open, closed, semi-closed or semi-open i.e. the
domain may be an interval of any of the following types.

If x ε [q, p], then {x : q < x < p}

If x ε (-∞, p], then {x : x < p}

If x ε (-∞, p), then {x : x < p}

If x ε ]-∞, p[, then {x : x < p}


If x ε (p, ∞], then {x : x > p}

If x ε (-∞, ∞), then {x : x ε R}

If x ε {p, q}, then {x : x = p or x q}

Domain of function 'f' is normally represented as Domain (f). Range is represented as


Range (f). Note that sometimes domain of the function is not explicitly defined. In
these cases domain would mean the set of values of 'x' for which f(x) assumes real
values. e.g. if y = f(x) then Domain (f) = {x : f(x) is a real number}.

e.g. Let X = {a, b, c}, Y = {x, y, z}. Suppose f(a) = y, f(a) = x, f(b) = y, f(c) = z.
Then f is not a function of X into Y since a ε X has more than one f-images in Y.

On the other hand, if we set f(a) = x, f(b) = x and f(c) = x, then f:X → is a function
since each element in X has exactly one f-image in Y.

Consider the following examples:

(i) Let X = R, Y = R and y = f(x) = x2.

Then f : X → Y is a function since each element in X has exactly one f-image in Y.


The range of f = {f(x) : x ε X} = {x2 : x ε R} = [0, ∞).

(ii) Let X = R+, Y = R+ and y = √x. Then f : X → Y is a function. The range of f is


R+

(iii) Let X = R, Y = R and y2 = x. Her f(x) = +√x i.e. f is not a function of X into Y
since each x > 0 has two f-images in Y, and further, each x < 0 has no f-image in Y.

We are primarily interested in functions whose domain and ranges are subsets of real
numbers. Such functions are often called Real Valued functions.

e.g. Let the function f be defined by f(x) = 1/√(2x+6).

In this formula we must have 2x + 6 > 0 and therefore x > -3. Therefore, the
domain of f is (-3, ∞), the range of f = (0, ∞). Thus we have the function f : (-3, ∞)
→ (0, ∞) defined by f(x) = 1/√(2x+6).

Let the function f be defined by f(x) = x/((x-1)(x-2)). The formula makes sense for
all values of x except x = 1 and x = 2. Therefore, the domain of f is R - {1, 2}
Functions: one-one/many-one/into/onto

Functions can be classified according to their images and pre-images relationships.


Consider the function x → f(x) = y with the domain A and co-domain B.

If for each x ε A there exist only one image y ε B and each y ε B has a unique
pre-image x ε A (i.e. no two elements of A have the same image in B), then f is said
to be one-one function. Otherwise f is many-to-one function.

e.g. x → x3, x ε R is one-one function

while x → x2, x ε R is many-to-one function. (see figure above)

e.g. x = + 2, y = x2 = 4

Graphically, if a line parallel to x axis cuts the graph of f(x) at more than one point
then f(x) is many-to-one function and if a line parallel to y-axis cuts the graph at
more than one place, then it is not a function.

For a one-to-one function

If x1 ≠ x2 then f(x1) ≠ f(x2)

or if (x1) = f(x2) => x1 = x2

One-to-one mapping is called injection (or injective).

Mapping (when a function is represented using Venn-diagrams then it is called


mapping), defined between sets X and Y such that Y has at least one element 'y'
which is not the f-image of X are called into mappings.

Let a function be defined as: f : X → Y

Where X = {2, 3, 5, 7} and Y = {3, 4, 6, 8, 9, 11}

The mapping is shown in the figure below.

Clearly, element 9 and 11 of Y are not the f-image of any of x ε X

So the mapping is into-mapping

Hence for into mappings:

f[X} Y and f[X] ≠ Y. => f [X] Y that is range is not a proper subset of co-
domain.

The mapping of 'f' is said to be onto if every element of Y is the f-image of at


least one element of X. Onto mapping are also called surjection.

One-one and onto mapping are called bijection.

Illustration
Check whether y = f(x) = x3; f : R → R is one-one/many-one/into/onto
function.

We are given domain and co-domain of 'f' as a set of real numbers.

For one-one function:

Let x1, x2 ε Df and f(x1) = f(x2)

=>X13 =X23

=> x1 = x2

i.e. f is one-one (injective) function.

For onto-into:

Ltx→a y = Ltx→a (x)3 = α

Ltx→a y= Ltx→a (X)3 = -α

Therefore y = x3 is bijective function.

Illustration:

What kind of function does the Venn diagram in figure given below represent?

Solution: This many-one into function

Domain = Df = {a, b, c}

Co-domain = {1, 2, 3}

Range = Rf = {1, 2}

f(a) = 1 ; f(b) = 2; f(c) = 2


Examples

Classify the following functions.

Ans.

(i) Many-one and onto (surjective).

(ii) One-one (injective) and into.

(iii) One-one (injective) and onto (surjective) i.e. Bijective.

(iv) and (v) are not functions.

Examples

1. Given the sets A = {1, 2, 3, 4} and B = {a, b, c} construct a

(i) Many-one into

(ii) many-one onto function


2. Given the sets c = {1, 2, 3} and D = {a, b, c}

(i) How many one-one onto functions can be constructed.

(ii) How many-one into functions can be constructed.

Ans.1

f:A→B f:A→B

2. (i) 6

(ii) 33 - 6 = 21

Illustration:

What is the domain and range of the following functions?

(a) y = 3x + 5 (b) y = (x2 +x)/(x2 - x)

Domain of y = f(x) is the set of values of x for which y is real and finite.

Range is the set of values of y for which x is real and finite.

Solution:

(a) For all real and finite x, y is also real and finite

Therefore Df = R = (-∞, ∞) and Rf = R = (-∞,∞)

(b) y = (x(x+1))/(x(x-1)) = (x+1)/(x-1) , x ≠ 0

when x = 0, y is 0/0 from (i.e. indetermined form)

when x = 1, y = ∞ (infinite)

Therefore Df = R -{0, 1}

also xy - y = x + 1

=> x (y - 1) = y + 1
x = (y+1)/(y-1)

when y = 1, x = ∞ (infinite) => y ≠ 1

also, for ≠ 0 => y ≠ -1

Therefore Rf = R - {-1, 1}

Illustration:

What is the domain of the following functions?

(a) y =√((x-1)(3-x)) (b) √(((x-1)(x-5))/(x-3)) (c) y= √sin x

Solution:

(a) y is real and finite if (x - 1)(3 - x) > 0

or (x - 1)(x - 3) < 0

i.e. x - 1 < 0 and x - 3 > 0 or x - 1 > 0 and x - 3 < 0

=> x < 1 and x > 3 => 1 < x < 3

which is not possible => 1 < x < 3

=> Df = [1, 3]

(b) Numerator becomes zero for x = 1, x = 5

Denominator becomes zero for x = 3

These three points divide x-axes into four intervals

(-∞, 1), (1, 3), (3, 5), (5, ∞)


Therefore Df = [1, 3) υ [5, ∞); at x = 3, we here open interval,

Because at x = 3, y is infinite.

(c) y = √sin x

sin x > 0 ∀ x ε [2n∏, (2n + 1) ∏], n ε I

Examples

1. What is domain of the following?

(a) y =√((x-1)(3-x)) (b) y = √xsinx (c) y = Sin-1((1+x2)/(2x))

2. What is domain and range of the following?

(a) (b) y =|x

Ans.

1. (a) Df = [1, 3)

(b) Df = [-(2n-1)∏, -2(n-1)∏] υ [2n ∏, (2n + 1)∏], nεN

(c) Df = {-1, 1}

2. (a) Df = [a, b[ and Rf = [c, d]

(b) Df = {0, 1, 2, 3, 4,......}

Rf = {1, 2, 6, 24, ......}


Increasing or decreasing function

The function f is said to be an increasing function in its domain D if

∀ x2 > x1 => f(x2) > f(x1); x1, x2 ε D

However if

∀ x2 > x1 => f(x2) > f(x1), x1, x2 ε D

The function 'f' is said to be strictly increasing

The function 'f' is said to be decreasing function in its domain D if

∀ x2 > x1 => f(x2) < f(x1); x1, x2 ε D


However if

∀ x2 > x1 => f(x2) < f(x1); x1, x2 ε D

Then it said to be strictly decreasing.

Strictly increasing and decreasing functions are also called Monotonic Function.

Illustration:

Is y = 2x + 3 increasing/decreasing function.

Solution:

Since, ∀ x ε R, y ε R

Therefore Df = R

Let x2 > x1; x1, x2 ε R

=> 2x2 > 2x1

=> 2x2 + 3 > 2x1 + 3

=> f(x2) > f(x1)


=> y = f(x) = 2x + 3 is strictly increasing function.

Examples

1. Are the following function increasing/decreasing?

(a) y = x3 + 8 (b) y = -2x + 4

Ans. (a) Decreasing

(b) Strictly decreasing

Let f : X → Y be a function defined by y = f(x) such that f is both one - one and
onto. Then there exists a unique function g : Y → X such that for each y ε Y,

g(y) = x <=> y = f(x). The function g so defined is called the inverse of f.

Further, if g is the inverse of f, then f is the inverse of g and the two functions f and
g are said to be the inverses of each other. For the inverse of a function to exists,
the function must be on-one and onto.

Method to Find Inverse of a Function

If f-1 be the inverse of f, then fof-1 = f-1 of = I, where I is an identity function.

fof-1 = I => (fof-1(x)) = I (x) = x.

Apply the formula of f on f-1 (x), we will get an equation in f-1 (x) and x.

Solve it to get f-1 (x).

Note : A function and its inverse are always symmetric with respect to the line y
= x.
Illustration: Let f : R → R defined by f(x) = (ex-e-x)/2 . Find f-1 (x).

Solution: We have f(f-1(x)) = x

=> (ef-1(x) - e-f-1(x))/2 = x

=> e2f-1(x) - 2xef-1(x) -1 = 0

=> ef-1(x) = x + √(x2 +1).

But negative sign is not possible because L.H.S. is always positive.

Thus ef-1(x) = x + √(x2 +1) . Hence, f-1(x) = log(x + √(x2 +1)) .

We give below some standard functions along with their inverse functions:

FUNCTIONS INVERSE FUNCTION


2
1. f:[0,∞)→[0,∞) defined by f(x)=x f :[0,∞)→[0,∞) defined by f-1(x) = √x
-1

2. f:[-∏/2,∏/2] →[-1,1] defined by f1 [-1,1]→[-(∏/2),∏/2] defined by f-


1
f(x)=sin x (x)=sin-1x

3. f:[0,∏]→[-1,1] defined by f(x)=sinx f1:[-1,1]→[0,∏] defined by f1(x)=cos-1x


4. f:[-∏/2,∏/2] →(-∞,∞) defined by f1:(-∞,∞)→[-(∏/2),∏/2] defined by
f(x)=tan x f1(x)=tan-1 x

5. f:(0,∏)→(-∞,∞) defined by f(x) = cot f-1:(-∞, ∞)→(0,∏) defined by f-1(x)=cot-


1
x x

6. f:[0,∏/2)U(n/2,n]→(-∞, -1]U[1,∞) f-1:(-∞,-1]U[1,∞) →[0,∏/2)U(∏/2,∏]


defined by f(x) = sec x defined by f-1 (x) = sec-1 x

7. f:[-(∏/2),0)(0,n/2]→(-∞,-1]U[1,∞) f-1:(-∞,-1]U[1,∞) →[0,-(∏/2))U(0,∏/2]


defined by f(x) = cosec x defined by f-1 (x) = cosec-1 x

8. f:R → R+ defined by f(x) = ex f-1(x):R+ → R defined by f-1 (x) = In x.

Invertible function
Let us define a function y = f(x): X → Y. If we define a function g(y) such that x =
g(y) then g is said to be the inverse function of 'f'.

Think: If f is many-to-one, g : Y → X will not satisfy the definition of a function.

So to define the inverse of a function, it must be one-one.

Further if f : X → Y is into then there must be a point in Y for which there is no x.


This again violates the definition of function for 'g' (In fact when f is one tone and
onto then 'g' can be defined from range of f to domain of i.e. g : f(X) → X.

Hence, the inverse of a function can be defined within the same sets for x and Y
only when it is one-one and onto or Bijective.

Note: A monotonic function i.e. bijection function is always invertible.

Illustration: Let f : R → R be defined as

y = f(x) = x2. Is it invertible?

Solution:

No it is not invertible because this is a many one into function

This is many-one because for x = + a, y = a2, this is into because y does not take
the negative real values.

Illustration: Let f : R → [0, α) be defined as y = f(x) = x2. Is it invertible?


(see figure below)

Solution:

No it is not invertible, it because it is many one onto function.


Illustration: Let f : [0, α) → [0, α) be defined as y = f(x) = x2. Is it invertible? If so
find its inverse.

Solution:

Yes, it is invertible because this is bijection function. Its graph is shown in figure
given below.

Let y = x2 (say f(x))

=> x = +√y

But x is positive, as domain of f is [0, α)

=> x = + √y

Therefore Inverse is y = √x = g(x)

Figure (A)

f(g(x)) = f(√x) = x, x> 0

g(f(x)) = g(x2) = √x2 = x, x > 0

i.e. if f and g are inverse of each other then f(g(x)) = g(f(x)) = x

Illustration: How are the graphs of function and the inverse function related? These
graphs are mirror images of each other about the line y = x.
Solution:

Also, if the graph of y = f(x) and y = f-1 (x), they intersect at the point where y meet
the line y = x.

Figure (B)

Graphs of the function and its inverse are shown in figures given above as Figure (A)
and (B)

For Figure (A)

y = f(x) = x2; f : [0, ∞) → [0, ∞)

Examples

1. Define y = f(x) = x2 in some other ay so that its inverse is possible.

2. What is the inverse of y = loge (x + √(x2 + 1))

Ans.1 f : (-α, 0] → [0, α)

y = f(x) = x2 and its inverse is

y = -√x (Figure B)

Ans.2 y = (ex - ex)/2


Even And Odd Function

A function f(x) : X → Y defined such that

f(-x) = f(x) ∀ x ε X

is called an even function and

if f (-x) = -d(x) ∀ x ε x, then the function f(x) is called an odd function.

Graphically, an even function is symmetrical w.r.t. y-axis and odd function is


symmetrical w.r.t. origin.

Note : In general all functions can be represented as sum of an even function


and an odd function.

Let, a function be defined as y = f(x). It can be written as:

=> y = (f(x) + f(-x))/2 + (f(x) - f(-x))/2

y = F1(x) + F2(x)

Whereas,

F1(-x) = (f(x) + f(-x))/2 = F1(x)

And F2(-x) = (f(-x) - f(x))/2

= -((f(x) - f(x))/2)

= -F2(x).

Here F1(x) is an even function and F2(x) is an odd function.

Exercise

State whether the following functions are odd or even or neither.

(1) y = x3
(2) y = x4

(3) y + x + cos x

(4) y = loge(x + √(x2 + 1))


Explicit and implicit functions

If, in a function the dependent variable y can be explicitly written in terms of


independent variable x i.e. terms of 'x' must not involve y in any manner then the
function is called an explicit function e.g.

y = x2 + 1

y = sin x + cos x

If the dependent variable y and independent variable x are so convoluted in an


equation that y cannot be written explicitly as function of x then f(x) is said to be an
implicit function.

e.g. x2 + y2 = tan-1 xy.

Periodic function
These are the function, whose value repeats after a fixed constant interval called
period, and which makes a class of a widely used function.

A function f of x, such that:

f(T + x) = f(x) ∀ x ε domain of f.

The least positive real value of T for, which above relation is true, is called the
fundamental period or just the period of the function.

e.g. for f(x) = sin x ∀ x ε R.

We know that sin (2∏ + x) = sin x, ∀ x ε R

so f(x) = sin x is a periodic function with a period of 2∏ radians.

Rules for finding the period of the periodic functions

(i) If f(x) is periodic with period p, then a f(x) + b, where a, b ε R (a≠0) is also a
periodic function with period p.

(ii) If f(x) is periodic with period, then f(ax + b), where a ε R -{0} and b ε R, is also
periodic with period p/|a|.

(iii) let us suppose that f(x) is periodic with period p and g(x) is periodic with period
q. Let r be the L.C.M. of p and q, if it exists.

(a) If f(x) and g(x) cannot be interchanged by adding a least positive number k,
then r is the period of f(x) + g(x).

(b) If f(x) and g(x) can be interchanged by adding a least positive number k and if
k < r, then k is the period of f(x) + g(x). Otherwise r is the period.

Illustration: Find the period of the following functions

(i) f(x) = sinx + {x}

(ii) f(x) = tan(x/3) + sin 2x.

(iii) f(x) = |sinx| + |cosx|

(iv) f(x) = ((1+sin x)(1+sec x))/((1+cos x)(1+cosec x))


Solution:

(i) Here f(x) = sinx + {x}

Period of sinx is 2p and that of {x} is 1. But the L.C.M. of 2p and 1 does not exist.
Hence sinx + {x} is not periodic.

(ii) Here f(x) = tanx/3 + sin2x. Here tan(x/3). Here tan(x/3) is periodic with period
3p and sin2x is periodic with period p.

Hence f(x) will be periodic with period 3p.

(iii) Here f(x) = |sinx| + |cosx|

Now, |sinx| = √sin2x = √((1+cos2x)/2), which is periodic with period ∏.

Similarly, |cosx| is periodic with period ∏.

Hence, according to rule of LCM, period of f(x) must be ∏.

But |sin((∏/2)+x)| = |cos x| and |cos((∏/2)+x)| = |sin x|.

Since ∏/2 < ∏, period of f(x) is ∏/2.

(iv) f(x) =((1+sin x)(1+sec x))/((1+cos x)(1+cosec x)) =

((1+sin x)(1+cos x)sin x)/((1+cos x)(1+sin x)cos x) = tan x

Hence f(x) has period ∏.

Note: For f(x) = |sin x| + |cos x|

The period of both |sin x| and |cos x| is ∏

But they are related with phase difference ∏/2 i.e.

|sin x| = |cos (x + ∏/2)|


|cos x| = |sin (x + ∏/2)|

So the period of the function f(x) is ∏/2.

Illustration: Prove that the period of y = sin x is 2∏

Solution:

Let T be the period of f(x) = sin x

i.e. f(T + x) = f(x)

=> sin (T + x) = sin x

=> T + x = n∏ + (-1)nx, n ε 1 .........(i)

Let n=0

T+x=x

=> T = 0

But we want a positive real value for T.

Let n = 1,

T+x=∏-x

=> T - ∏ = 2x (Is it possible? Think)

No it is not possible because LHS is constant and RHS is a continuous variable.

Now, Let n = 2 in equation (i)

T + x = 2∏ + x

=> T = 2∏

Therefore period of y = sin x is 2∏

Note: If we cannot find T independent of x, then y = f(x) is not periodic.

Example
Find the period of y = cos √x and y = x sin x if possible

Ans. These are non-periodic function


Bounded and unbounded function

Let a function be defined as f(x): A → B and we can find two real numbers m and
M such that m < f(x) < M ∀ x ε A then f(x) is called the bounded function. m and M
are called the lower-bound and the upper-bound of f(x) respectively. The range of
f(x) is [m, M] (see figure given below), If however, m and M or either of them is not
defined (i.e. infinite) then f(x) is said to be unbounded function.

Constant function and the Identity function


The function f: R → a where 'a' is a constant, is called a constant function. It is
denoted by f(x) = a. The graph of a constant function is as shown in the figure given
below; clearly a constant function is all-to-one.

The function f(x): R → R defined such that f(x) = x ∀ x ε R is an Identify


function. The graph of an identity function is shown in the figure given below.

Since an identity function is on-one and onto, so it is invertible.

Note: The inverse of an identity function is the identity function itself.

Examples

Check whether the following functions are identical with their inverse.

(a) xy = 1

(b) x2 + y2 = 1

Ans. (a) Yes


(b) only for 0 < x < 1, 0 < y < 1
Absolute Value Function

The function defined as:

is called an absolute value function.

Note : √x2 = |x| ∀ x ε R

The graph of an absolute value function is shown in the figure given above. Its
properties are:

(i) An absolute value function is an even function

(ii) It is strictly increasing in [0, ∞) and strictly decreasing in (-∞, 0].

Illustration 12: Draw the graph of the following functions.

(a) y = |x - 1| + |x - 4|

(b) y = |sin x|

(c) y = sin |x|

(a) Note: x - 1 = 0 => x = 1 and x - 4 = 0 => x = 4 i.e. y changes its definition


at x =1 and x = 4.

y = |x - 1| + |x - 4|

let - ∞ < x < 1

y = -(x - 1) - (x - 4) = -2x + 5
Now, let 1 < x < 4

y = (x - 1) - (x - 4) = 3

Again, Let 4 < x

y = (x - 1) + (x - 4) = 2x - 5

(b) y = |sin x|

y>0∀xεR

(c) y = sin |x|

∀ x > 0, y = sin x

∀ x < 0, y = sin (-x) = -sinx


Signum Function

The signum function is defined as f(x) = |x|/x; x≠0

= 0; x=0

is called the signum function

The graph of a signum function is as shown in the figure given above.


Polynomial And Rational Function

A function of the form

y = a0 + a1x + a2x2 + ......... + an-1xn-1 + anxn

where ai ε R (I = 0, 1, 2, ........., n) and an ≠ 0 is called a polynomial function of

degree n. The domain of every polynomial function is R.

x → P(x)/Q(x) , Q(x) ≠ 0.

Linear Function

When the degree of P(x) and Q(x) in a rational function, are one then it is called a
linear function.

So, the linear fraction is defined as

f(x) = (ax+b)/(cx+d)

Domain of linear fraction function is R - {-d/c}

And its range is R - {a/c} (Therefore x = (b-dy)/(cy-a)).

Exponential Function
Exponential and Logarithmic Functions:

The function f(x) = ax, a > 0 where the base 'a' is constant and index x is a
variable, is called an exponential function.

Clearly, x ε R so domain of f(x) is R and for no value of x, f(x) < 0 so range of


'f' is R - (-∞, 0] or (0, ∞)

Graph of an exponential function: y = ax:

The graph is different for 0 < a < 1 and a > 1, so we will discuss these cases
separately.

Case I. a>1

Let a = 2. The domain is [-∞, ∞].

The value table is as given below

X ... -3 -2 -1 0 1 2 3 4 5 6 ... ...


f(x) ... 1/8 ¼ ½ 1 2 4 8 16 32 64 ... ...

Note:

(i) The curve approaches x-axis as x → -∞

So x-axis i.e. line y = 0 is the asymptote of y = ax. for a > 1

(ii) This function is increasing strictly as x increases.


So, it is a strictly increasing function, hence invertible.

Case II: 0<a<1

Let a = 1/2 Domain of f is (-∞, ∞) The value table is as under

X -3 -2 -1 0 1 2 3
f(x) 8 4 2 1 ½ ¼ 1/8

We observe that

(i) As x becomes very large, f(x) approaches x axis

i.e. y = 0 is the asymptote of f(x) for a < 1

(ii) y = ax decreases strictly as x increases for 0 < a < 1

So it is a strictly decreasing function. Hence, y = ax is a monotonic function for any a


≠ 1.

For a < 0 the exponential function in not defined precisely and for a = 1 it turns out
to be constant function.
We have observed that y = ax is a monotonic function (either strictly) decreasing or
strictly increasing). Hence it is invertible,

So y = ax <=> x = loga y

Where x ε [-∞,∞ ] and y ε [0, ∞]

The inverse exponential function x = loga y is known as logarithmic function.


Writing it in conventional form it becomes

y = loga x = f(x), x ε [0,∞]

The inverse exponential function x = loga y is known as logarithmic function.


Writing it in conventional form it becomes

y = loga x = f(x), x ε [0, ∞].

Properties of logarithmic Function:

(i) y = logb x is defined for x > 0, b > 0, b ≠ 1.

(ii) if logb a = c then a = bc

(iii) logb 1 = 0

(iv) logb b = 1

(v) logb a = 1/loga b

(vi) logb xy = logb x + logb y

(vii) logb XY = logb x - logb y

(viii) logb xm = m logb x

(ix) logbn x = 1/n logb x

(x) logb bx = x

(xi) (b)logbx = x
Illustration: Prove logb a = 1/loga b

Solution:

Let c = logb a and d = loga b

=> a = bc and b = ad

=> a = bc and a = b(1/d)

=> c = 1/d

=> logb a = 1/loga b

Illustration: Prove logb xm = m logb x

Solution:

Let c = logb xm and d = logb x

=> xm = bc and x = (b)d

=> ((b)d)m = bc

=> md = c

=> logb xm = m logb x.


Greatest Integer Function

The function f(x) : R → Z defined as:

f(x) = [x] = greatest integer less than or equal to x is called the greatest
integer function. The graph of a greatest integer function is shown in figure given
below. The graph shows that it is increasing (not strictly) many-to-one function.

Illustration: Let [x + 1] = 3 then find x.

Solution:

From definition of greatest integer function

3<x+1<4

=> 2 < x < 3

Note : Any number x can be written as

x = [x] + (x)

where [ ] denotes the integral part

and ( ) denotes the fractional part

i.e.

[3.7] = 3

(3,7) = 0.7

[-3,7] = -4

(-3.7) = 0.3.
Note : 0 < (x) < 1

∀ -2 < x < -1 => [x] = -2

∀ -1 < x < 0 => [x] = -1

∀ 0 < x < 1 => [x] = 0

∀ 1 < x < 2 => [x] = 1

∀ 2 < x < 3 => [x] =2

∀ n < x < n + 1 => [x] = n, n ε I

Examples

1. [x + 1] = [x] + 1 ∀ x ε R True/False

2. |-(x/∏)| = -1-|x/∏|, x ≠ n ∏ , n ε I True/False

3. If [(x) + x] = 3 then x =? where [ ] represents greatest integer function and


( ) represents integer greater than or equal to x.

Ans.1 True

Ans.2 True

Ans.3 1<x<2
Graphical representation of a Function

The function f : R - {0} → R is represented in the graph such that the x co-ordinate
represents the independent variable and the y co-ordinate represents the dependent
variable. The graph of the function shows various properties of the function directly
and more clearly. The limiting case of the graph of the function is represented by an
asymptote:

Asymptote is a straight line to which graph of the function approaches at infinity but
does not exactly touch it as shown in figure shown above.

Coordinate axis x = 0 is asymptotes to the graph of y = 1/x.

We consider some examples of functions and their graphs

S.No. FUNCTION DOMAN, RANGE GRAPH


AND DEFINITION
1. A Constant Function f : R → {c}

defined by f{x} = c

2. The Identity Function f:R→R

defined by f(x) = x

3. The Absolute Value f : R → [0, ∞)


Function
defined by f(x) = |x|
4. The Exponential f : R → (0, ∞)
Function
defined by f(x) = ex

5. The Natural f: (0, ∞) → R


Logarithmic
defined by f(x) = In x

6. The Greatest Integer f:R→Z


Function
defined by f(x) = [x]

the greatest
integer< x

7. The Fractional part of f:R→R


x
defined by f(x) = {x}

8. Polynomial Functions f(x) = a0xn + a1xn-1 + .... + an-1 x + an

where a0, a1, ......, an are real numbers, a0 ≠ 0.


9. Rational Functions f(x) = p(x)/q(x), where p(x) and q(x) are polynomials
in x. Domain is R - {x : q(x) = 0}

10. Trigonometric or Circular Functions:


11. Inverse circular Functions
Composite Functions

Another useful combination of two functions f and g is the composition of these two
functions. Let f : X → Y and g : Y → Z be two functions.

We define a function h : X → Z by setting h(x) = g(f(x). To obtain h(x), we first take


the f-image f(x), of an element x in X so that f(x) ε Y, which is the domain of g(x)
and then take the g-image of f(x), that is, g(f(x)), which is an element of Z. The
scheme is shown in the figure.

The function h, defined above, is called the composition of f and g and is written gof.
Thus (gof)(x) = g(f(x)). Domain of gof = {x : x in domain f, f(x) in domain g}.

e.g. Let f : R → R be a function defined by f(x) = x2 + 4 and g[0, ∞) → R be a


function defined by g(x) = √x. Then gof(x) = g(f(x)) = √(x2 + 4). Domain of gof = R.
Thus we have gof : R → R defined by (gof)(x) = √(x2 + 4). Similarly, we shall have
fog : [0, ∞) → R defined by (fog)(x) = x + 4. Note that (gof)(x) ≠ (fog)(x).

Illustration: Two functions are defined as under :

Find fog and gof.

Solution: (fog)(x) = f(g(x))

Let us consider, g(x) < 1 :

(i) x2 < 1, -1 < x < 2 => -1 < x < 1, -1 < x < 2 => -1 < x < 1

(ii) x2 + 2 < 1, 2 < x < 3 => x < -1, 2 < x < 3 => x = φ

Let us consider, 1 < g(x) < 2,

(iii) 1 < x2 < 2, -1 < x < 2


=> x ε [-√2, -1) υ (1,√2] , -1 < x < 2 => 1 < x < √2

(iv) 1 < x+2 < 2, 2 < x < 3 => -1 < x < 0, 2 < x < 3, x = φ

Let us consider -1 < f(x) < 2 :

(i) -1 < x+1 < 2, x < 1 => -2 < x < 1, x < 1 => -2 < x < 1

(ii) -1 < 2x+1 < 2, 1 < x < 2 => -1 , x < ½, 1 < x < 2 => x= φ

Let us consider 2 < f(x) < 3:

(iii) 2 < x+1 < 3 , x < 1 => x < 2 , x < 1 => x = 1

(iv) 2 < 2x+1 < 3, 1 < x < 2 => 1 < 2x < 2, 1 < x < 2

=> ½ < x < 1 , 1 < x < 2 => x = φ

If we like we can also write g(f(x)) = (x+1)2, -2 < x < 1.

Problem of finding out fog and gof can also be handled using graphical
methods

f(g(x))
Here g(x) becomes the variable that means we would draw the graph of g(x). It is
clear that g(x) < 1 ∀ x ε [-1, 1] and 1 < g(x) < 2 ∀ x ε (1, √2]

In this case f(x) becomes the variable and we will draw the graph of f(x). From the
graph we observe that -1 < f(x) < 2 ∀ x ε [-2, 1) and f(x) = x + 1.

2 < f(x)) < 3 => x = 1 and f(x) = x + 1.

i.e. g(f(x)) = (x + 1)2, -2 < x < 1


Basic Transformations on Graphs

Drawing the graph of y = f(x) + b, b ε R, from the known graph of y = f(x)

It is obvious that domain of f(x) and f(x) + b are the same. Let us take any point x0in
the domain of f(x). y|x=x0 = f(x0).

The corresponding point on f(x) + b would be f(x0) + b.

For b > 0 => f(x0) + b > f(x0) it means that the corresponding point on
f(x) + b would be lying at a distance 'b' units above point on f(x).

For b > 0 => f(x0) + b < f(x0) it means that the corresponding point on
f(x) + b would be lying at a distance 'b' units below point on f(x).

Accordingly the graph of f(x) + b can be obtained by translating the graph of f(x)
either in the positive y-axis direction (if b > 0) or in the negative y-axis direction (if b
< 0), through a distance |b| units.

Drawing the graph of y = |f(x)| from the known graph of y = f(x)

|f(x)| = f(x) if f(x) > 0 and |f(x)| = -f(x) if f(x) < 0. It means that the graph of f(x)
and |f(x)| would coincide if f(x) > 0 and the portions where f(x) < 0 would get
inverted in the upwards direction.
The above figure would make the procedure clear.

Drawing the graph of y = f(|x|) from the known graph of y = f(x)

It is clear that, f(|x|) =

Thus f(|x|) would be a even function. Graphs of f(|x|) and f(x) would be identical in
the first and the fourth quadrants (as x > 0) and as such the graph of f(|x|) would be
symmetrical about the y-axis (as (|x|) is even).

The figure would make the procedure clear.

Drawing the graph of |y| = f(x) from the known graph of y = f(x)

Clearly |y| > 0. If f(x) < 0, graph of |y| = f(x) would not exist. And if
f(x) > 0, |y| = f(x) would give y = + f(x). Hence graph of |y| = f(x) would exist only
in the regions where f(x) is non-negative and will be reflected about the x-axis only in
those regions.
Drawing the graph of y = f(x + a), a ε R from the known graph of y = f(x)

Let us take any point x0 ε domain of f(x), and set x + a = x0 or x = x0 - a.


a > 0 => x < x0, and a < 0 => x > x0. That mean x0 and x0 - a would given us
same abscissa for f(x) and f(x + a) respectively.

As such, for a > 0, graph of f(x + a) can be obtained simply by translating the graph
of f(x) in the negative x-direction through a distance 'a' units. If a < 0, graph of f(x
+ a) can be obtained by translating the graph of f(x) in the positive x-direction
through a distance a units.

Drawing the graph of y = a f(x) from the known graph of y = f(x)


It is clear that the corresponding points (points with same x co-ordinates) would
have their ordinates in the ratio of 1 : a.

Drawing the graph of y = f(ax) from the known graph of y = f(x)

Let us take any point x0 ε domain of f(x). Let ax = x0 or x = x0/a.

Clearly if 0 < a < 1 then x > x0 and f(x) will stretch by 1/a units against the y-axis,
and if a > 1, x < x0, then f(x) will compress by a units against the y-axis.

Drawing the graph of y = f-1(x) from the known graph of y = f(x)

For drawing the graph of y = f-1(x) we have to first of all find the interval in which
the function is bijective (invertible). Then take the reflection of y = f(x) (within the
invertible region) about the line y = x. The reflected part would give us the graph of
y = f-1(x).

e.g. let us draw the graph of y = sin-1 x. We know that y = f(x) = sin x is invertible if
f : [-∏/2, ∏/2] → [-1, 1], => the inverse mapping would be f-1 : [-1, 1]→[-∏/2,
∏/2].
Illustration: Draw the graph of f(x) = cosx cos(x + 2) - cos2(x + 1).

Solution : f(x) = cox cos(x + 2) - cos2(x + 1)

1/2 [cos(2x + 2) + cos 2]

-(1/2)[cos(2x + 2) + 1]

= (1/2) cos 2 -(1/2) < 0.

Solved Examples

Example 1:

Given are two sets A {1, 2, -2, 3} and B = {1, 2, 3, 5}. Is the function f(x) = 2x - 1
defined from A to B?

Solution :

Out of all the ordered pairs, the ordered pairs which are related by the function f(x) =
2x - 1 are {(1, 1), (2, 3), (3, 5) But for (-2) in A, we do not have any value in B. So,
this function does not exist from
A->B.

Example 2:

A function f is defined as f: N -> N (where N is natural number set) and f(x) = x+2.
Is this function ONTO?

Solution :

Since, N = {1, 2, 3, 4, .........} and A = B = N

For : A->B

When x = 1 f(x) = 3

When x = 2 f(x) = 4

So f(x) never assume values 1 and 2. So, B have two elements which do not have
any pre-image in A. So, it is not an ONTO function.

Example 3 :

Find the range and domain of the function f(x) = (2x+1)/(x-1) and also find its
inverse.

Solution :

This function is not defined for x = 1. So, domain of the function is


R -{1}.

Now, for finding the range

Let,(2x+3)/(x-1) = y

=> 2x + 3 = yx - y

=> yx - 2x = y + 3

=> (y - 2)x = y + 3

=> x =(y+3)/(t-2)

So, y cannot assume value 2

Range of f(x) is R - {2}.

Inverse is y =(x+3/x-2) .
Example 4:

Find domain and range of the function f(x) = (x2+2x+3)/(x2-3x+2)

Solution :

This function can be written as : f(x) =(x2+2x+3)/(x-1)(x-2) .

So, domain of f(x) is R - {1, 2}

For range, let (x2+2x+3)/(x2-3x+2) = y

=> (1 - y)x2 + (2x + 3y) x + 3 - 2y = 0

for x to be real, Discriminant of this equation must be > 0

D>0

=> (2 + 3y)2 - 4(1 - y)(3 -2y) > 0

=> 4 + 9y2 + 12y - 4(3 + 2y2 - 5y) > 0

=> y2 + 32y - 8 > 0

=> (y + 16)2 - 264 > 0

=> y < - 16 - √264 or y > - 16 + √264.

Example 5 :

Find the period of following functions

(a) cos3 x + sin 5 x

(b) |cos x| + |sin2 x|

(c) x - |x|.

Solution :

(a) f(x) = cos 3x + sin 5x

period of cos 3x = 2∏/3 and period of sin 5x = 2∏/53

L.C.M. of 2∏/3 and 2∏/5 is 2p

So period of f(x) is 2p.


Note: Let g(x) = cos 3x

g((2∏/3)+x) = cos3 ((2∏/3)+x)

= cos (2∏ + 3x)

= cos 3x

= g(x)

(b) f(x) = |cos x| + |sin2 x|

Period of |cos x| = ∏

Period of |sin 2 x| = ∏/2

So, period of f(x) is ∏

(c) f(x) = x [x]

Let T be the period of this function

=> f(T + x) = f(x)

=> T + x - [T + x] = x - [x]

=> T = [T + x] - [x] .......... (1)

=> T = integer - integer

= integer

Let T = 1 (Therefore 1 is the smallest positive integer)

Equation (1) becomes

1 = [1 + x] - [x]

which is true for all x ε R

Period of f(x) is 1.

Example 6:

Show that the inverse of a linear fraction function is always a linear fraction function
(except where it is not defined).

Solution:
Let, f(x) = (a+bx)/(c+dx) be the said linear fraction function.

Let at some x it attains value y, so,

(a+bx)/(c+dx) = y

=> a + bx - cy - dxy = 0

=> a - cy + x (b - dy) = 0

=> x = (cy-a)/(b-dy).

Which is again a linear fraction function defined in R except

at x = -c/d and y = b/d

and inverse of the given function is, y = (cx-a)/(b-dx).

Example 7:

If graph of function f(x) is as shown in the figure given below, then plot the graph of
|f(x)|.

f(x) + 1, f(x + 2) and f-1 (x)

Solution:

(a) |f(x)| will reflect the graph of f(x) below x axis to the (-) ve y axis side. So the
graph will be as shown in the figure given below.
(b) f(x) + 1 will just shift the graph by one unit position up. So the required graph
is as shown in the figure given below.

(c) f(x + 2) will shift the graph of f(x) by two units to left, the graph will be as
shown in the figure given below.

(d) f-1(x) is obtained by reflection of graph f(x) on the line y = x as shown in the
figure given below.
Example 8:

Show that the following functions are even

(a) f(x) = x2/(2x2-1) + x2/2 + 1

(b) f(x) = (ax+a-x)/2

(c) f(x) = x2 - |x|

Solution:

(a) f(x) = x2/(2x2-1) + x2/2 + 1

so, f(-x) = (-x)2/(2(-x)2-1) + (-x)2/2 + 1

= x2/(2x2-1) + x2/2 + 1 = f(x)

so, f(x) in sum function.

(b) f(x) = (ax+a-x)/2

=> f(-x) = (a-x+ax)/2 = f(x)

so, f(x) is even function

(c) f(x) = x2 - |x|

=> f (-x) = (-x)2 - |-x| = x2 - |x| = f(x)

so, f(x) is even function.

Example 9:

Show that following functions are odd.

(a) f(x) = (ex-1)/(ex+1)

(b) f(x) = log((1-x)/(1+x))

(c) f(x) = √(1+x+x2) - √(1-x+x2)

Solution:

(a) f(x) = (ex-1)/(ex+1)


=> f(x) = (e-x-1)/(e-x+1) = (1-ex)/(1+ex)

= -((ex-1)/(ex+1)) = -f(x)

=> f(-x) = -f(x)

=> so, f(x) is an odd function

(b) f(x) = log ((1-x)/(1+x))

=> f(-x) = log((1+x)/(1-x)) log((1-x)/(1+x))-1

=> -log((1-x)/(1+x))

=> f(-x) = -f(x)

so, f(x) is an odd function.

(c) f(x) = √(1+x+x2) - √(1-x+x2)

f(-x) = √(x2-x+1) - √(1+x+x2)

= -[√(1+x+x2) - √(1-x+x2)]

f(-x) = -f(x)

so, f(x) is an odd function

Example 10:

If f(x) = 1 + x; 0 < x < 2

= 3 - x; 2 < x < 3

Determine

(a) g(x) = f(f(x))

(b) f(f(f(x)))

(c) f([x])

(d) [f(x)]

Where [ ] represents the greatest integer function.

Solution:
(b) Let 0 < x < 1

f(f(f(x)))

= f(2 + x) 2 < 2 + x < 3

But we observe that there is no single definition f(f(x)) for this interval.

Therefore we reduce the interval 0 < x < 1 to 0 < x < 1.

Let 0 < x < 1

f(f(f(x)))

= f(2 + x); 2 < x + 2 < 3

= 3 - (2 + x)
=1-x

Let 1 < x < 2

= f(2 - x); 0 < 2 - x < 1

=1+2-x

=3-x

Let 2 < x < 3

= f(f(f(x)))

= f(4 - x); 1 < 4 - x < 2

= 1 + (4 - x)

=5-x

Let x = 0

f(f(f(x))) = f(f(1)) = f(2) = 3

(c) f([x])

Let 0 < x < 1

f[x] = f(0) = 1

Let 1 < x < 2

f[x] = f(1) = 2

Let 2 < x < 3

f[x] = f(2) = 3

Let x = 3

f([x]) = f(3) = 0
(d) [f(x)]

First draw the graph of y = f(x)

Let 0<x<1

1 < f(x) < 2 => [f(x)] = 1

Let 1<x<2

2 < f(x) < 3 => [f(x)] = 2

Let x=2

f(x) = 3

[f(x)] = 3

Let 2<x<3

0 < f(x) < 1 => [f(x)] = 0

Example 11:

If x2 + y2 = 1

prove that - √2 < x + y <√2 .


Solution:

Since, x2 + y2 = 1 => x = cos θ, y = sin θ

Consider,

x + y = cos θ + sin θ

= √2((1/√2)sinθ + (1/√2)cosθ )

= √2sin((∏/4) + θ)

Recall : sin((∏/4)+θ) can take maximum value 1 and minimum value -1.

=>|√2 sin((∏/4)+θ)| ≤ √2

=> - √2 < x + y < √2. Hence proved.

Example 12:

Check the invertibility of the function f(x) = (ex - e-x); and then find its inverse.

Solution:

We have

f(x) = ex - e-x; x ε R

limx->α f(x) = α

limx->-α f(x) = -α

f'(x) = ex + e-x > 0 ∀ ∑ R

Therefore f : R -> R

f(x) = ex - e-x is a bijective function

Therefore f(x) is invertible

Now, f(x) = y = t - 1/t [where t = ex]

=> t2 - 1 = ty

=> t2 - ty - 1 = 0
=> t = (y+√(y2+4))/2 [t cannot be negative]

Now

t = ex

=> ex = (y+√(y2+4))/2

=> x = loge ((y+√(y2+4))/2)

Therefore Inverse of y = ex - e-x is y = loge ((x+√(x2+4))/2)

Example 13:

If f(x) = ((1-x)/(1+x)) x ≠ 1 and x ε R.

Then show that

(i) f(1/x) = -f(x), x ≠ 0

(ii) f(f(x)) + f(f(1/x)) > 2 for x > 0.

Solution:

f(x) = (1-x)/(1+x), x ≠ 1 and x ε R

=> f(1/x) = (1-(1/x))/(1+(1/x)) = (x-1)/(x+1), x ≠ 0

=> - f(x)

Now f(f(x)) = (1-(1-x)/(1+x))/(1+(1-x)/(1+x)) = (2x)/2 = x

and f(f(1/x)) = (1-(x-1))/(1+x))/(1+(x-1)/(1+x)) = 2/2x = 1/x

=> f(f(x)) + f(f(1/x)) = x + 1/x

= (√x-(1/√x))2 + 2

R.H.S. = 2 + a positive number > 2

so f(f(x)) + f(f(1/x)) > 2

Example 14:

Let A = R - {3},
B = R - {1}, let f: A -> B be defined by f(x) = (x-2)/(x-3). Is f bijective? Give
reasons.

Solution:

(a) Let us test the function for injectivity

Let x1, x2 ε A and f(x1) = f(x2)

=>( x1-2)/(x1-3) = (x2-2)/(x2-3)

=> x1 = x2

Therefore f is one-one function (injective) .........(1)

(b) Let us test the function for surjectivity

Let y be any arbitrary element of B and suppose there exists an x such that f(x) = y

(x-2)/(x-3) = y => x = (3y-2)/(y-1)

since y ≠ 1, x is real

Also, x ≠ 3, for if x = 3, then 3 = (3y-2)/(y-1)

or 3y - 3 = 3y - 2 => - 3 = - 2, which is false

Thus x = (3y-2)/(y-1) ε A such that f(x) = y i.e. ∀ y ε B, we have x ε A.

and so f is surjective

This proves that f is bijective.

Tricky Examples

Example 15:

Show that if an odd function is invertible, then its inverse is also an odd
function.

Solution:
Let y = f(x) be an odd function

Then

f(-x) = -f(x) = -y

Since it is invertible, so we can write

x = g(y)

Where g(x) = f-1 (x)

Consider,

g(-y) = g(-f(x))

= g(f(-x)) = -x = -g(y)

So g(x) is also an odd function.

Example 16:

Sketch the graph of each of the following functions

(a) f(x) = x4 - 2x2 + 3

(b) f(x) = 2x/(1+x2)

(c) f(x) = sin2x - 2sinx.

Solution:

(a) y = f(x) = x4 - 2x2 + 3

(i) Domain of f(x) is R

(ii) f(x) is even so graph will be symmetrical about y axis.

(iii) y = x4 - 2x2 + 3 = (x2 - 1)2 + 2.

So minimum value of y is at x2 = 1(x = + 1).


(iv) When x = 0 the value of y = 3

The graph of the function is as shown in fig.

(b) y = f(x) = 2x/(1+x2).

(i) Domain = R

(ii) f(x) = -f(x), so function is odd the graph is not symmetric about any axis
but symmetric about origin.

So it is sufficient to consider only. x > 0

(iii) y = 0 when x = 0 there is no other point of intersection with co-


ordinate axes.

(iv) As (x - 2)2 > 0

=> x2 + 1 > 2x

So 2x/(x2+1) < 1 and equality holds at x = 1. Also from 0 to 1 the function


increases and from 1 to a it decreases. So the graph is as shown in fig.

(c) y = f(x) = sin2 x - 2sinx

(i) Domain of y is R

(ii) 0 < (sin x - 1)2 < 4


=> 0 < sin2 x - 2sinx + 1 < 4

=> -1 < sin2 x - 2sinx < 3

(iii) f(x) has period 2∏ so it is

Sufficient to draw the graph for domain [0, 2∏]

(iv) y = 0 for x = 0, n∏

Note : More about increasing/decreasing we shall study in Module 5.

Example 17:

Solve (x)2 = [x]2 + 2x

Where [x] represents greatest integer less than or equal to x.

(x) represents integer just greater than or equal to x.

Solution:

Method 1:

Case I :

Let x = n ε I

=> Given equation becomes:

n2 = n2 + 2n

=> n = 0

Case II:
Let x ε I

i.e. n < x < n + 1

Given equation becomes:

(n - 1)2 = n2 + 2x

=> x = n + 1/2, n ε I

Therefore x = 0 or x = n + 1/2; n ε I

Method 2:

Case I :

x I

x = [x] + {x}; where {x} represent fraction part of x.

x = (x) - (1 - {x})

(x + 1 - {x})2 = (x - {x})2 + 2x (Using given equation)

=> (x + 1 - {x})2 + 1 + 2 (x - {x})2 = (x - {x})2 + 2x

=> 1 - 2 {x} = 0

=> {x} = 1/2

x = n + 1/2, n ε I

Also, x = 0, by observation.

Example 18:

Find the set x if the function f:[2, α] -> x where f(x) = 5 - 4x + x2 is bijective.

Solution:

y = x2 - 4x + 5

= (x - 2)2 + 1

When x = 2, y = 1

As x ε [2, α) then y ε [1, α]


Therefore Set X ≡ [1, α)